FOOTBALL IN FICTION - MCGOWAN, LEE. ([S.l.] : ROUTLEDGE, 2019)
Football in Fiction represents the most comprehensive historical mapping and analysis of novels related to association football (soccer). It offers a theoretically informed field guide, a scholarly cartography of football fiction's uncertain -and until now -only partially explored terrain. Combining an extensive search for texts with up-to-date academic research, journals, surveys, catalogues, and reviews the book demonstrates a topographic perspective of the field - one that captures and establishes its breadth, depth, and distinctive identity. The book uses and adapts two distinct reading models of abstraction, in conjunction with closer textual analyses. Together they assist in realising a set of demonstrable conventions, outline a taxonomy of fictive types, establish the genre's current state of play, and advance the football novel as a form with its own literary history and traditions. This book is a valuable resource for those studying and researching in the areas of the social and cultural aspects of football, sports fiction, sports writing, creative writing, and literary and genre studies. Furthermore, related industry professionals will find this a fascinating read, particularly football writers, fans of the sport, and those interested in sports history and cultural phenomena.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / General; SPORTS & RECREATION / General; SPORTS & RECREATION / History; Soccer in literature; Fiction -- History and criticism; Sports literature -- History and criticism